The Role of Advanced Imaging in Paediatric Cardiology: Basic Principles and Indications - Kavga, Maria; Ramcharan, Tristan; Papadopoulou-Legbelou, Kyriaki (Journal of Cardiology and Cardiovascular Medicine, 2023)
Tissue Doppler Imaging and Speckle Tracking Echocardiography are newer echo-cardiographic modalities, that assess myocardial and valvular function in congenital and acquired heart diseases in childhood. In addition, cross-sectional imaging including Cardiac Magnetic Resonance (CMR) and Cardiac Computed Tomography has been widely used over the last decade in paediatric cardiology, in order to evaluate intra-cardiac and extra-cardiac anatomy. Cardiac Magnetic Resonance particularly allows detailed analysis of myocardial function, and shunt quantification and has applications even in fetal life. This mini-review summarizes the basic principles of the above-advanced modalities and highlights their main indications and clinical applications in childhood.